PERAN GURU DALAM KURIKULUM 2013 - Alawiyah, Faridah (Jurnal Aspirasi, 2013)
The Government has developed a new curriculum that will be implemented in 2013. The new curriculum has reduced the role of teacher, as teachers would not be mainly exercising their roles as technical officers. This is different compare to teachers’ role during KBK and KTSP. The latest curriculum wouldopen anopportunity for teachers to improve and optimize their roleswithin the classrooms. In the end, it will optimize the effectiveness of learning and improve the quality of education for it first will improve teachers’ competencies.